The Social Purposes of Learning Assessment - Abulencia, Arthur S (ATIKAN, 2011)
ABSTRACT: Assessment has been studied by many researchers and educators from the prism of educational theories which means a purely instructional or pedagogical analysis of assessment. But there is an open space in which learning assessment could be further scrutinized using sociological perspective, so that we could explore and expose the social roles of assessment. This discussion is engaged in the analysis of the social consequences of assessment and its resistances from the various participants of teaching and learning process. Assessment has been widely used for accountability, control, and sorting mechanism of society to distribute the limited social positions that are available. Thus, only those students who are properly equipped with knowledge, values, and competencies are the ones who excel in the assessment devices. Students in the lower echelon of society are left with limited opportunities for social mobility and employment, due to their limited capacity to pass through this filtering machine called assessment. So, there some manifest and latent resistances that students as well as teachers about the negative consequences of assessment. Thus, assessment is not only a system to improve learning, account teachers, and schools but rather is an instrument of academic segregation and tracking. Assessment should be viewed beyond the walls of classroom by looking at the close but intricate linkage of assessment and society. Since assessment is a social fact, therefore, we need to consider how it is developed and practiced in everyday life of teachers and students. Education is never neutral, according to Paulo Freire, and also assessment is can never be neutral. It is resisted by some sector of society, but it is still a very strong mechanism to classify and rank people in a society. It serves a purpose in perpetuating a societyâs present order as well as a site to perturb the existing order by its results.Â  KEY WORD: Assessment, social roles and purposes of assessment, academic performance, and resistance of assessment. Â Assistant Professor Arthur S. Abulencia is a Lecturer at the Faculty of Social Sciences Education PNU (Philippine Normal University), Taft Avenue, Manila 1000, Philippine. He can be reached at: arthurpnu@yahoo.com and asabulencia@gmail.comHow to cite this article? Abulencia, Arthur S. (2011). âThe Social Purposes of Learning Assessmentâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.1(1) Juni, pp.105-122. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, ISSN 2088-1290. Chronicle of the article: Accepted (April 11, 2011); Revised (May 19, 2011); and Published (June 5, 2011).